Study on qualitative simulation technology of group safety behaviors and the related software platform. (January 2019) - Yu, Kai; Cao, Qinggui; Zhou, Lujie
Highlights: The qualitative simulation algorithm based on QSIM are optimized by GA-BP. The universal software platform for qualitative simulation is developed. The study has been used to simulate and analyze the safety behavior of coal miners. Abstract: The qualitative simulation technology of group safety behaviors is very important for investigating the laws of safety behaviors, and its application software is an essential tool for the research. Based on the QSIM algorithm and the related theories in the social field force, this study optimizes the filtering process of QSIM algorithm using the GA-BP algorithm (Genetic algorithm-BP neural network), and establishes a complete qualitative simulation system of group safety behaviors. In this study, a qualitative simulation software platform of group safety behaviors is designed and established. Moreover, the simulation results using different algorithm are analyzed and compared, and the statistical charts are plotted for displaying the development trend and evolution laws of group safety behaviors. According to the experimental qualitative simulation results on group safety behaviors of coal miners, the proposed qualitative simulation technology of group safety behaviors can improve efficiency and reliability of the qualitative simulation. The developed software platform can provide a convenient and effective qualitative simulation tool for further exploring the laws of group safety behaviors.